Access to genitourinary medicine clinics in the United Kingdom. Issue 1 (1st February 2001) - Foley, Elizabeth; Patel, Raj; Green, Neville; Rowen, David
Abstract : Objectives: To assess the variability in time taken for a patient to be seen in a genitourinary (GUM) clinic in the United Kingdom having contacted that clinic by telephone and compare this with GUM physicians' expectations. Methods: A postal questionnaire was sent to lead GUM physicians asking when they thought patients with two specific clinical scenarios would be seen in their clinics. Following this, healthcare personnel contacted individual units posing as patients with the same clinical scenarios and asked to be seen as soon as possible. Results: 202/258 (78%) lead clinicians responded to the postal questionnaire. All clinics claimed to have procedures allowing patients with acute symptoms to be assessed urgently and estimated that such patients would be seen within 48 hours of the initial telephone contact. In 243 of 311 (78%) clinic contacts, the patient was invited to attend the clinic within 48 hours. For the remaining 68 contacts (22%) the patient could not be accommodated within 48 hours and, of these, 49 could not be seen for more than 1 week. Conclusions: No clinician estimated that patients with acute severe symptoms would be seen more than 48 hours after the initial telephone contact, but in reality, for 22% of the patient contacts this was the case. This study may well underestimate the difficulties the general public may have in accessing GUM services. We hypothesise that this situation could be ameliorated by establishing process standards and addressing issues of resource allocation.